Enhanced anti-fouling and catalytic performance of nanocomposite membrane to improve water purification - Goh, Natalie Sze Min (Nanyang Technological University, 2024)
This project addresses the critical challenges faced by polymeric membranes in water filtration, namely membrane fouling. This phenomenon is caused by the accumulation of unwanted contaminants, resulting in diminished filtration efficiency, higher operational costs for maintenance and reduced lifespan. In response to this challenge, this project examined the performance of Cellulose Acetate (CA) membrane, together with MXene-Cellulose Acetate (MXene-CA) membrane and Cobalt (II) Hydroxycarbonate-MXene-Cellulose Acetate (Co2(OH)2CO3-MXene-CA) membrane. The latter membranes are CA membranes that had been enhanced with MXene through vacuum filtration and Co2(OH)2CO3-MXene through hydrothermal treatment & vacuum filtration respectively. In this project, the membranes underwent a comprehensive series of performance & characterisation tests and analyses such as the Deionised (DI) Water & Acid Orange 7 (AO7) Flux Tests, AO7 Particle Rejection Test, AO7 Visual Test & Ultraviolet-Visible (UV-VIS) Spectroscopy Test, Catalytic Membrane Reliability Test, Video Contact Angle (VCA) Analysis, Field Emission Scanning Electron Microscopy (FESEM) Analysis and Energy Dispersive X-ray (EDX) Analysis. From the results, the Co2(OH)2CO3-MXene-CA membrane proves to be the best among the membranes, showing improved permeability as well as superior particle rejection properties. Furthermore, this membrane exhibits exceptional anti-fouling properties, and it also has self-cleaning properties that provide a way for solving some maintenance-related challenges encountered in membrane technology. Overall, the project underlines how surface modification of nanomaterials in membranes improves membrane technology and thus provides a viable sustainable solution for water treatment and purification. The findings underscore the potential of the Co2(OH)2CO3-MXene- CA membrane as an attractive option for practical applications because it exhibits excellent performance attributes crucial to addressing the challenges faced in water treatment and purification on a wider scale.